1996
DOI: 10.1177/104063879600800411
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive Criteria for Antimicrobial Susceptibility Testing of Ceftiofur against Bacteria Associated with Swine Respiratory Disease

Abstract: Abstract. Ceftiofur, an extended-spectrum cephalosporin, is active against a variety of animal pathogens, including organisms associated with swine respiratory disease. However, minimum inhibitory concentration (MIC) breakpoint and disk diffusion interpretive criteria have not been established for swine pathogens. Susceptibility tests were performed by broth microdilution MIC and disk diffusion methods on 246 bacterial species that cause swine respiratory disease. Ceftiofur was active against Salmonella sp., P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…Previous studies conducted in other countries report similar results (Blanco et al, 1997;Tadesse et al, 2012). Ceftiofur, a third-generation cephem antibiotic, was first approved in 1988 for veterinary use in food animals to treat a variety of Gram-negative bacterial infections (Burton et al, 1996). Studies have shown that ceftiofur use in animals can select for extendedspectrum cephem resistance in bacteria isolated from animals and humans (Winokur et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies conducted in other countries report similar results (Blanco et al, 1997;Tadesse et al, 2012). Ceftiofur, a third-generation cephem antibiotic, was first approved in 1988 for veterinary use in food animals to treat a variety of Gram-negative bacterial infections (Burton et al, 1996). Studies have shown that ceftiofur use in animals can select for extendedspectrum cephem resistance in bacteria isolated from animals and humans (Winokur et al, 2001).…”
Section: Discussionmentioning
confidence: 65%
“…At the same time, broad-spectrum antibiotics, such as ceftiofur, florfenicol, and enrofloxacin are commonly used against many diseases in domestic animals, including the poultry flock (Booker et al, 1997;Burton et al, 1996;el-Banna, 1998;Graham et al, 1988;Ueda and Suenaga, 1995;Vancutsem et al, 1990). Sometimes, they are also administered at the time of vaccination.…”
Section: Introductionmentioning
confidence: 98%
“…It has been known to have many pharmacological activities, including anti-microbial and anti-inflammatory activities [8]. It has been widely used to treat a broad array of infectious diseases caused by Gram-positive and Gram-negative bacteria, such as pneumonia, peritonitis and mastitis in dairy cattle [8,9]. We have previously shown that ceftiofur can inhibit LPS-stimulated TNF-α, IL-1β and IL-6 secretion in RAW264.7 cells via activation of the NF-κB and MAP-kinase pathways [10].…”
Section: Introductionmentioning
confidence: 99%